Study of Reptile and Amphibian Diversity at Ledok Amprong Poncokusumo, Malang East Java - Luhur Septiadi; Berry Fakhry Hanifa; Ainul Khatimah; Yunita Indawati; Muhammad Zakaria Alwi; Muhammad Prayogi Erfanda (University of Brawijaya, 2018)
Malang is one of the areas that have a high diversity of reptiles and amphibians because of the strategic ecosystem but still minimal in terms of research publications. The purpose of this study was to know the diversity of reptiles and amphibian through the existence of herpetofauna species, microhabitat and indicator species. Data was collected during the rainy season, once a month in the period of three months from October 2017 to January 2018 at night. Data collection was conducted using the Virtual Encounter Survey method with different zones and limited by time. The collected specimens were identified with the guidance of literatures. The collected specimens were then preserved at the Animal Physiology Laboratory, Department of Biology, State Islamic University of Maulana Malik Ibrahim Malang. Then, the data was analyzed to obtain the diversity index, frequency and dominance. The result showed that the number of reptiles found in the location site was seven species consisting of Famili Gekkonidae, Scincidae, Agamidae and Elapidae. Mean while for the species of amphibians, it was obtained nine species consisting of Famili Bufonidae, Ranidae, Rhacophoridae, Dicroglossidae, and Microhylidae. The ecosystem consisted of four habitat types including terrestrial, arboreal, semi-aquatic and aquatic. However, based on the value of diversity index, relative frequency, and dominance value, as well as the indicator species, this area has a relatively low diversity, the disturbed environment and therefore conservation efforts need to be undertaken.